Bite Incidents and Farmer-Reported Crop Damage by Rhesus Macaques in Lansdowne Forest Division, Uttarakhand, India - Rathi, Robin; Kukreti, Mohan (Journal of Agriculture and Forestry University, 2026)
Monkeys play a crucial role in the ongoing conflict between humans and wildlife across the globe. This article examines the dynamics of human-monkey conflicts (HMC) within the Lansdowne Forest Division (LFD), drawing on data collected from 2015 to 2018 on reported bite incidents involving rhesus macaques (Macaca mulatta). Descriptive analysis showed that males aged 16 to 35 were more frequently involved in reported bite incidents compared to females of the same age group. Moreover, many respondents reported substantial local crop raiding; farmers reported, perception-based estimates indicate that in some localities approximately 70% of the agricultural lands in the region have been affected by rhesus macaques foraging; these values were not validated by field measurements. Habitat destruction and improper disposal of human waste likely contribute to this conflict. To effectively address these issues, it is essential to develop sustainable strategies that balance the needs of local communities with the imperative of conserving monkey populations.